(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
To identify the directions of groundwater flows and the exact location of groundwater wells in the volcanic regions of the Republic of Armenia, on the example of territory of Aragats Massif, correlation links were found from geophysical field and well data. For this purpose, mathematical-statistical methods with non-uniform location (distribution) of field data of electrical probe points were used. The results contribute to the fixing the location of groundwater wells.